EKSPLORASI HUBUNGAN FEAR OF MISSING OUT (FOMO), PENGARUH SELEBRITI, DAN LIMITED EDITION TERHADAP PURCHASE INTENTION BONEKA LABUBU PADA KOMUNITAS LABUBU DI MEDIA SOSIAL - Dahlia Luftiani; Setiawan, Aries; Safitri, Maria; Wibowo, Mochammad Eric Suryakencana (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
This study aims to examine the relationship between fear of missing out (FOMO), celebrity influence, and limited editions on the purchase intention of Labubu dolls. Data were collected from 107 respondents within the Labubu fan community on social media using a combination of purposive sampling and snowball sampling methods. Data collection was conducted through questionnaires, and the analysis was performed using SPSS software, including validity and reliability tests, classical assumption tests, and hypothesis testing. The results of the study indicate that FOMO, celebrity influence, and limited editions collectively have a significant relationship with Labubu purchase intention. These findings highlight the importance of leveraging marketing strategies based on FOMO and limited editions, as well as collaborations with celebrities, to enhance product appeal and drive sales. This research provides practical guidance for businesses in developing effective marketing strategies.